2007
DOI: 10.1128/jcm.01318-06
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Class I Integrons among Pseudomonas aeruginosa and Acinetobacter baumannii Isolates from Patients in Nanjing, China

Abstract: Class I integrons were detected in 40.8% (40/98) of Pseudomonas aeruginosa strains and 52.8% (56/106) of Acinetobacter baumannii strains in the Nanjing area of China, including several cassette arrays not previously reported.The rapid dissemination of antibiotic resistance genes among bacterial isolates is an increasing problem in infectious disease. Recent studies have shown that a conserved DNA sequence, integron, may be carried on these episomal genetic structures (12,14). Integrons possess two conserved se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
97
4
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 13 publications
21
97
4
10
Order By: Relevance
“…Recent studies have shown that resistance genes might have been carried by an integron. Many resistance genes exist as gene cassettes within integrons, which may themselves be located on transmissible plasmids and transposons [36]. Production of an integrinmediated β-lactamases from different molecular classes (carbenicillinases and extended-spectrum β-lactamases belonging to class A, class D oxacillinases and class B carbapenem hydrolysing enzymes) and synthesis of aminoglycoside modifying enzymes (phosphoryl-transferases, acetyltransferases and adenylyltransferases) are some of the resistance mechanisms in P. aeruginosa [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that resistance genes might have been carried by an integron. Many resistance genes exist as gene cassettes within integrons, which may themselves be located on transmissible plasmids and transposons [36]. Production of an integrinmediated β-lactamases from different molecular classes (carbenicillinases and extended-spectrum β-lactamases belonging to class A, class D oxacillinases and class B carbapenem hydrolysing enzymes) and synthesis of aminoglycoside modifying enzymes (phosphoryl-transferases, acetyltransferases and adenylyltransferases) are some of the resistance mechanisms in P. aeruginosa [37].…”
Section: Discussionmentioning
confidence: 99%
“…In China, resistance to various antibiotics is common in clinical isolates, often more so than in western countries, especially among the most common causes of hospitalacquired opportunistic pathogens such as Enterobacteriaceae, Pseudomonas aeruginosa and Acinetobacter baumannii [8,9]. Over the past decades, much work has been done on the epidemiology of integrons and their important roles in bacterial resistance in both clinical and natural environments [2,4,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, much work has been done on the epidemiology of integrons and their important roles in bacterial resistance in both clinical and natural environments [2,4,[8][9][10][11]. Surveillance of integrons therefore is essential for the investigation of MDR bacteria evolution.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the presence of integrons in our isolates, PCR-RFLP was performed by using the degenerate primers hep35 and hep36 (Table 1). The expected amplicon size (491 bp) was ascertained by electrophoresis on a 1.5 % agarose gel with appropriate molecular size markers (100 bp DNA ladder; MBI Fermentas), and the PCR products were further restricted using HinfI (MBI Fermentas) to determine the class of integron (Gu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To identify the presence of integrons in our isolates, PCR-RFLP was performed by using the degenerate primers hep35 and hep36 (Table 1). The expected amplicon size (491 bp) was ascertained by electrophoresis on a 1.5 % agarose gel with appropriate molecular size markers (100 bp DNA ladder; MBI Fermentas), and the PCR products were further restricted using HinfI (MBI Fermentas) to determine the class of integron (Gu et al, 2007).Amplification and sequencing of gene cassette regions. The gene cassettes of the class 1 integron were amplified using specific primers for 59 and 39 conserved segments (59CS and 39CS; Table 1) combined with primers VIM-R/IMP-R and VIM-F/IMP-F, respectively (Pitout et al, 2007).…”
mentioning
confidence: 99%